Squeak Learn Programming with Robots - Ducasse, Stephane. (Apress : Imprint: Apress, 2005)
Are you completely new to programming? Do you want to have fun learning to program? Squeak: Learn Programming with Robots will teach you core programming concepts based on simple, visual problems that involve manipulation of robots, or "turtles." You will learn basic programming concepts like loops, abstractions, composition, and conditionals. Each chapter is structured so that it can be turned into a one- or two-hour lab session. And while the structured content explains solid principles of object-oriented programming, you'll just have fun going through the sequence of easy examples with the turtle. And be sure to check out BotsInc, the companion learning environment for this book.